Assessment of Insecticide Compatibility with Beauveria bassiana for Fall Armyworm (Spodoptera frugiperda) Management in Maize - G. Sugeetha; M. V. Adwaitha; K. S. Nikhil Reddy; P. Mahadevu; J. Mahadevu (International Journal of Economic Plants)
The study was conducted during March–April, 2021, in College of Agriculture, V. C. Farm, Mandya, Karnataka, India to assess their combined efficacy and potential synergistic or antagonistic effects. The compatibility between Beauveria bassiana and various insecticides was evaluated at 7, 14, and 21 days after inoculation to assess fungal growth inhibition and colony diameter for the management of maize fall armyworm (FAW). The results revealed that, at 7 days post-inoculation, significant differences were observed in fungal growth inhibition among all insecticide combinations with Beauveria bassiana. The inhibitory effects varied from 26 to 68% with Chlorantraniliprole 9.3+ λ-cyhalothrin 4.6 ZC at half recommended concentration (RC) exhibiting the least inhibition (26%) and good colony growth (33.3 mm). At 14 days post-inoculation, all treatments displayed significant differences compared to the control, with growth inhibition ranging from 15.67 to 62.7%. Chlorantraniliprole 9.3+λ-cyhalothrin 4.6 ZC at half RC exhibited the least inhibition (15.67%) and promoted larger colony growth. At 21 days post-inoculation, significant differences persisted among treatments, with Chlorantraniliprole 9.3+λ-cyhalothrin 4.6 ZC demonstrating high compatibility and harmlessness towards B. bassiana, even at lower concentrations. In contrast, Novaluron 5.25+Emamectin benzoate 0.9 SC exhibited the highest growth inhibition (59%) at full RC. Hence, the study accomplishes the combination of Chlorantraniliprole 9.3+λ-cyhalothrin 4.6 ZC, especially at lower concentrations, demonstrated high compatibility with B. bassiana, offering an effective and sustainable approach for managing FAW.